WORKSHOP COILING EXERCISES ON TENNIS SPIN SERVE WITH KINOVEA - Ians Aprilo; Arifuddin Usman; Syahruddin Syahruddin; Hikmad Hakim; Poppy Elisano Arfanda; M. Adam Mappaompo (Bajang Institute, 2023)
The main problem is that service is only considered as the beginning of a match. When in fact service is a very important thing in a match, because service is a fast way to get points. One important part of the tennis serve is the skill of coiling or body rotation. The purpose of this service is to provide coiling exercises that are analyzed kinovea application. This service is carried out for 6 weeks with a frequency of 3 times per week. At the beginning and at the end of the meeting the partners' coiling skills were analyzed using the kinovea app. Partners are 30 South Sulawesi novice tennis athletes aged 14-16 years. The result of this dedication was an average increase in coiling skills of 1,267. So this service is necessary in improving coiling skills in order to be able to score points quickly in a match of tennis.